PENINGKATAN PROSES PEMBELAJARAN IPS MENGGUNAKAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DI KELAS IV SD NEGERI 05 ALANG RAMBAH KABUPATEN PESISIR SELATAN - Shella Marcelina; Silfi Melindawati; Rafhi Febryan Putera (Universitas Negeri Padang, 2018)
The purpose of this study is to describe the improvement of the social studies learning process by using a cooperative model of the Teams Games Tournament (TGT) type in fourth grade students of SD Negeri 05 Alang Rambah Pesisir Selatan. This study uses a type of classroom action research with quantitative and qualitative approaches, this study consisted of II cycles consisting of planning, implementation, observation and reflection. Data collection techniques are observation, tests and documentation. While the research instruments are observation sheets, test sheets and documents. The results of research from each cycle that was carried out showed an increase in the learning process. In planning the first cycle the average is 74.5% in the second cycle increased to 96.42%. In the implementation of learning on aspects of the teacher the first cycle the average is 78.5% and in the second cycle increased to 96%. Learning aspects of students in the first cycle were 78.5% and in the second cycle increased to 96%. On the learning outcomes of students in the first cycle the average was 66.68% and the second cycle increased to 81.36%. Thus it can be concluded that the use of the cooperative model type Teams Games Tournament (TGT) can improve the social studies learning process.Keywords: Cooperative Model Type Teams Games Tournament (TGT), IPS